EFEKTIVITAS PENGGUNAAN CONSTRUCTIVISM APPROACH TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI KELAS XI SMA NEGERI 7 PADANGSIDIMPUAN - Aisyah Rizky Harahap; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to know whether there is a significant influence of using constructivism approach on students’ mathematical communication ability at the eleventh grade students of SMA Negeri 7 Padangsidimpuan. The research was conducted by using experimental (pretest post test one group design) method with 24 students as the sample and they were taken by using purposive sampling technique from 115 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using constructivism approach was 2.50 (good category) and b) the average of students’ mathematical communication ability before using constructivism approach was 54.96 (enough category) and after using constructivism approach was 85.17 (very good category). Furthermore by using inferential statistic (Pair Sample ttest), it could be found significant value was less than 0.05 (0.000 <0.05). It means, there is a significant influence of using constructivism approach on students’ mathematical communication ability at the eleventh grade students of SMA Negeri 7 Padangsidimpuan.